Integrity Disclosure in Banking Companies in Indonesia - Christina Seva Pranata; Intiyas Utami; Natasia Alinsari (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
Fraudulent practices such as corruption can lead losses and are one of the obstacles to achieving company goals. This has a lot to do with a lack of integrity. Integrity is a concept related to a commitment to comply with the ethics, values, and norms in society. The purpose of this study is to identifythe integrity disclosure in banking companies in Indonesia. The research method is content analysis based on information from the bank’s official website. The measurement uses the Integrity Framework Disclosure Index (IFDi) which includes 13 indicators with 47 disclosure items. Integrity disclosure measurement is conducted on 107 online websites of Indonesian banking companies that are registered in the Financial Services Authority (OJK). The results of this study indicate that integrity disclosure in banking companies in Indonesia is high with an average score of 37 out of 47 disclosure items, or 79.44%. The state-owned bank group has the highest integrity disclosure with an average score of 44.25 out of 47 disclosure items.